2018
DOI: 10.1186/s12887-018-1352-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between asymptomatic rotavirus infection and jaundice in neonates: a retrospective study

Abstract: BackgroundRotavirus (RV) infection in neonates can be mild or even asymptomatic. In RV infection, jaundice is often reported, but the relationship between jaundice and RV infection has not been studied. This study aimed to determine the importance of asymptomatic RV screening in neonates with jaundice.MethodsNeonates from the neonatal intensive care unit (NICU) of Chonbuk National University Hospital, those transferred from local obstetrics and gynecology hospitals and outpatient clinics were selected from 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
3
0
2
Order By: Relevance
“…Although studies on jaundice caused by bacterial infections, especially urinary tract infection, have progressed, studies on jaundice caused by viral infections are limited ( 28 30 ). Hwang and Kim ( 31 ) reported a relationship between asymptomatic RV infection and jaundice in newborns. However, in the current study, the association between RV-negative antigen and jaundice was statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies on jaundice caused by bacterial infections, especially urinary tract infection, have progressed, studies on jaundice caused by viral infections are limited ( 28 30 ). Hwang and Kim ( 31 ) reported a relationship between asymptomatic RV infection and jaundice in newborns. However, in the current study, the association between RV-negative antigen and jaundice was statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Fever is known to be the most common symptom of rotavirus infection in newborns [ 8 , 9 , 13 ]. A recent study in Korea reported that rotavirus infection is frequently observed in newborns hospitalized for neonatal jaundice [ 14 ]. Rotavirus is the main neonatal gastroenteritis causing pathogen, and in this study, 40.4% of infants hospitalized for gastrointestinal system disease were rotavirus positive.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the surveillance of symptomatic and asymptomatic newborns is imperative. However, previous studies have had limited data on the epidemiology of rotavirus outbreaks, including the prevalence of symptomatic newborns with jaundice, gastroenteritis, and seizures [1,[8][9][10][11]14].…”
Section: Introductionmentioning
confidence: 99%
“…У новорожденных при ротавирусной инфекции редки тяжелые формы или летальный исход, заболевание может протекать в легкой форме (от 33 до 77 % больных младенцев) или бессимптомно. У инфицированных младенцев часто развивается желтуха [11,12].…”
unclassified
“…Союзом педиатров России в соответствии с поручением министра здравоохранения Российской Федерации подготовлены клинические рекомендации «Вакцинопрофилактика ротавирусной инфекции у детей» по применению зарегистрированной в Российской Федерации вакцины РотаТек ® (Вакцина для профилактики ротавирусной инфекции, пентавалентная, живая) производства Мерк Шарп и Доум Корп, США 12 .…”
unclassified